Effects of L-citrulline malate oral supplementation on post-exercise hypotension - Casonatto, Juliano; Góes, Renata Cristina; Grandolfi, Kamila; Cavalari, João Vagner (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: L-citrulline malate supplementation promotes an increase in oxide nitric metabolites, which are considered important mediators of peripheral vasodilation. Thus, the supplementation with this substance might maximize the duration and magnitude of post-exercise hypotension. Objectives: To investigate the hypotensive effect of L-citrulline malate supplementation following a single session of aerobic exercise in normotensives. Methods: Forty adults, normotensives, sedentary, were randomly assigned to one of the four experimental groups (control-placebo, control-Lcitrulline, exercise-placebo and exercise-Lcitrulline). All participants ingested a sachet with placebo or L-citrulline with malate (6 grams), both dissolved in water and the ingestion was made 120 minutes before starting the experimental session. The subjects performed 40 minutes of walk/run at 60-70% of reserve heart rate. For the control session, they remained seated in rest during 40 minutes. The blood pressure was taken in rest and every 10 minutes until complete 60 minutes after the experimental session. The ambulatory blood pressure device take the readings every 20 minutes (awake time) and each 30 minutes (sleep time) over the course of 24 hours. Results: L-citrulline malate supplementation associated to aerobic exercise promoted significantly reductions on systolic blood pressure when compared with control-placebo at 20 min (net change[NC]: 9.7 mmHg [P=0.010]), 40 min (NC: 12.7 mmHg [P=0.010]), 50 min (NC: 12.1 mmHg [P=0.012]), 60 min (NC: 9.0 mmHg [P=0.050]) and overall mean (NC: 7.8 mmHg [P=0.018]) post exercise. Conclusion: Acute L-citrulline malate supplementation might potentiate the post-exercise hypotension effects in normotensive subjects.